Search for the rare decays B0S → e+ e- and B0 → e+ e- - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kopecná, Renata; et al. (Physical review letters, 2020)
A search for the decays B0s→e+e− and B0→e+e− is performed using data collected with the LHCb experiment in proton-proton collisions at center-of-mass energies of 7, 8, and 13 TeV, corresponding to integrated luminosities of 1, 2, and 2 fb−1, respectively. No signal is observed. Assuming no contribution from B0→e+e− decays, an upper limit on the branching fraction B(B0s→e+e−)<9.4(11.2)×10−9 is obtained at 90(95)% confidence level. If no B0s→e+e− contribution is assumed, a limit of B(B0→e+e−)<2.5(3.0)×10−9 is determined at 90(95)% confidence level. These upper limits are more than one order of magnitude lower than the previous values.